تأثير إستراتـجيات معرفية والتلاعب الفكري فى تعليم اللغة العربية - محمد مصباح الدين (Arabic Literature Department, 2017)
Teaching is a knowledge and art. It is knowledge because all of its activities must be driven by scientific research findings, whereas it is artistic because of its applications on how the teaching is creative and singning a good impression. In order to this distinctive purpose, the good teaching need to several methods based on comprehensive and interdiciplinary research findings. This paper examines the influence of cognitif strategy and mind manipulation on Arabic language teaching. The finding shown by this paper is that the influence of both cognitif strategy and mind manipulation is significant. The significance of cognitif strategy is led by a number of actitivites i.e. practicing, receiving and delivering knowledge, analysing and concluding, arranging an input and output. In the other hand, the significance of mind manipulation is identified by a way the information is taken out, or the influencing on the subconscious is conducted, and by hypnotism and cultivation of ideas.